Neem formulation in management of insect infestation in cultivation of the oyster mushroom in Meghalaya - Bhat, M Narayan; Kumar, Sangit; Singh, A K; Chandra, satish; Shyesha, A N (Mushroom Research, 2015)
Please see the full text